2009
DOI: 10.1007/s12011-009-8386-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Heavy Metals on the Developmental Stages of Ovule and Seed Proteins in Chenopodium botrys L. (Chenopodiaceae)

Abstract: Excessive amounts of heavy metals adversely affect plant growth and development. Also, the presence of elevated levels of heavy metal ions triggers a wide range of cellular responses including changes in gene expression and synthesis of metal-detoxifying peptides. The overall objective of this research was to elucidate some microscopic effects of heavy metals on the formation, development, and structure of ovule and seed storage proteins in Chenopodium botrys L. To achieve this purpose, the surrounding area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…10b), which is in agreement with previous observations reported by Malayeri et al [13] about the effect of heavy metals on ovule in Euphorbia cheiradenia Boiss & Hohen and Yousefi et al [32] in C. botrys. As another sign of cell degeneration under toxic effect of heavy metals in polluted plants, a considerable vacuolation of embryonic cells was detected (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…10b), which is in agreement with previous observations reported by Malayeri et al [13] about the effect of heavy metals on ovule in Euphorbia cheiradenia Boiss & Hohen and Yousefi et al [32] in C. botrys. As another sign of cell degeneration under toxic effect of heavy metals in polluted plants, a considerable vacuolation of embryonic cells was detected (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The problems arise when cells are confronted with an excess of these vital ions or with non-nutritional ions that lead to cellular damages [26,27]. The toxic effects of metals on plants have been intensively studied at the level of biochemical, physiological, and histological processes such as photosynthesis [25,28], transpiration [29], enzyme activity [30], metal accumulation in tissue [22,31,32], or developmental process of sex organs [13,14]. The development of pollen and ovule is very important for plant reproductive survival so that any abnormality can cause a decrease in seed production and plant survival [11,33].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been conducted in order to evaluate the effects of different heavy metal concentrations on live plants [8][9][10], there are few reports about toxic effects of heavy metals on the developmental stages of sex organs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The switch to asexual reproduction itself is usually a selective disadvantage in adverse conditions but is sometimes maintained (Deng et al, 2007;Deschamps et al, 2007). Many authors have found various kinds of developmental disturbances and degenerative processes in anthers and ovules of pioneer colonizing plants, resulting in a high percentage of aborted ovules and anthers (Ostrolucká, 1989;Ostrolucká et al, 1995;Mičieta and Murin, 1996;Izmaiłow, 2000;Kościńska-Pająk, 2000;Czapik et al, 2002;Izmaiłow and Biskup, 2003;Biskup and Izmaiłow, 2004;Malayeri et al, 2005;Kłosowska et al, 2009;Yousefi et al, 2009), even though generative organs are highly protected regions of the plant organism (Ernst et al, 1992;Wierzbicka and Panufik, 1998;Sun et al, 2005). As the female gametophyte is a single few-celled structure enclosed in a small ovule, it is more convenient to examine microsporogenesis and male gametophyte development, which yield huge numbers of pollen grains.…”
Section: Introductionmentioning
confidence: 99%